An observational study of switching infliximab biosimilar: no adverse impact on inflammatory bowel disease control or drug levels with first or second switch. Issue 5 (5th July 2021) - Luber, Raphael P.; O'Neill, Rhona; Singh, Sukhpreet; Sharma, Esha; Cunningham, Georgina; Honap, Sailish; Meade, Susanna; Ray, Shuvra; Anderson, Simon H.; Mawdsley, Joel; Sanderson, Jeremy D.; Samaan, Mark A.; et al.
Summary: Background: Biologics account for a significant cost in inflammatory bowel disease (IBD) management; however, switching from infliximab originator to its biosimilars has enabled cost saving without compromising disease control. The effects on IBD activity and infliximab trough levels of a second switch to another biosimilar are, however, uncertain. Aims: To assess the effects on disease activity and infliximab trough levels associated with switching from infliximab biosimilar CT‐P13 to another biosimilar SB2 and compare outcomes in those switching for the first and second time. Methods: IBD patients on CT‐P13, including some previously switched from originator, were prospectively followed during a switch to SB2. C‐reactive protein (CRP), trough infliximab level and clinical disease activity indices were collected at baseline, Infusion 3 or 4 ('early' after switch), and 1 year. Results: One hundred eighty‐six patients (n = 99 second switch) on stable infliximab dosing underwent switching. Compared with baseline, there was no significant change in CRP, clinical disease activity scores or median trough infliximab level at the early time point among first‐switch (baseline vs early: 5.7 vs 6.6 µg/mL, P  = 0.05) and second‐switch (4.3 vs 4.9 µg/mL, P  = 0.07) patients nor at 1 year (median infliximab trough levels, baseline vs 1 year, in first‐switch [5.7 vs 5.7 µg/mL, P  = 0.37] and second‐switch [4.3 vs 4.7 µg/mL, P  = 0.06] patients). The proportion of patients in clinical remission did not significantly change at the early (92% vs 91% at baseline, P  = 0.75) or 1 year (95% vs 91% at baseline, P  = 0.16) time points. There was no significant difference in time to loss of response between patients switching for the first or second time ( P  = 0.69). Conclusions: Switching from one infliximab biosimilar to another had no adverse impact on infliximab trough levels, and clinical and biochemical disease activity, regardless of whether switching for the first or second time. Abstract : No significant difference in disease control or drug levels following first or second switch of infliximab biosimilar in IBD patients.